2023
DOI: 10.1021/acsomega.2c07233
|View full text |Cite
|
Sign up to set email alerts
|

Photo-on-Demand In Situ Synthesis of N-Substituted Trichloroacetamides with Tetrachloroethylene and Their Conversions to Ureas, Carbamates, and Polyurethanes

Abstract: N-substituted trichloroacetamides (NTCAs), which serve as blocked isocyanates, were synthesized in ∼97% yields by in situ photo-on-demand trichloroacetylation of amines with tetrachloroethylene (TCE). The reactions were performed by photo-irradiation of TCE solutions containing an amine under O2 bubbling over 70 °C with a low-pressure mercury lamp. TCE underwent photochemical oxidation to afford trichloroacetyl chloride having high toxicity and corrosivity, which then reacts in situ with the amine to afford NT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…This result is consistent with the fact that the ratio of COCl 2 in the photooxidation of TCE increased with increasing temperature as reported previously. 3 In contrast, the reaction was decelerated by increasing the concentration of TFE and pyridine to the ratio of 10:2:3 (entry 4). The reaction barely proceeded upon further increasing TFE and pyridine to the ratio of 10:5:7.5, probably due to the threshold concentration (entry 5).…”
Section: Photochemical Reactions With Mixtures Of Tce Alcohol and An ...mentioning
confidence: 99%
See 3 more Smart Citations
“…This result is consistent with the fact that the ratio of COCl 2 in the photooxidation of TCE increased with increasing temperature as reported previously. 3 In contrast, the reaction was decelerated by increasing the concentration of TFE and pyridine to the ratio of 10:2:3 (entry 4). The reaction barely proceeded upon further increasing TFE and pyridine to the ratio of 10:5:7.5, probably due to the threshold concentration (entry 5).…”
Section: Photochemical Reactions With Mixtures Of Tce Alcohol and An ...mentioning
confidence: 99%
“…Recently, we achieved the direct photochemical conversion of TCE to NTCA with a solution of TCE and amine [Scheme 1, reaction (II)]. 3 The obtained NTCAs could be converted to N-substituted ureas and carbamates via strong base-catalyzed condensation reactions with amines or alcohols. However, to the best of our knowledge, no example has been reported for the synthesis of carbonate esters from TCE via the reaction of TCAE and an alcohol.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction occurred efficiently in a short time upon irradiation of CHCl 3 under O 2 bubbling using UV-C light from a low-pressure mercury lamp (LPML). We then developed photo-on-demand in situ phosgenation reactions for synthesizing a variety of organic chemicals and polymers with CHCl 3 solutions containing both a substrate and an organic base [Scheme , reaction (c)]. Although alcohols such as EtOH serve to stabilize CHCl 3 , and the organic bases and solvents absorb UV-C light, , the phosgenation products were obtained in high yields through in situ reactions of the substrates and COCl 2 generated from CHCl 3 . These results indicated that the photochemical oxidation of CHCl 3 occurred not only in the liquid phase but also in the gas phase.…”
Section: Introductionmentioning
confidence: 99%